Transduction‐Specific ATLAS Reveals a Cohort of Highly Active L1 Retrotransposons in Human Populations. Issue 7 (23rd April 2013) - Macfarlane, Catriona M.; Collier, Pamela; Rahbari, Raheleh; Beck, Christine R.; Wagstaff, John F.; Igoe, Samantha; Moran, John V.; Badge, Richard M.
<x xml:space="preserve">Abstract</x> Long INterspersed Element‐1 (L1) retrotransposons are the only independently mobile elements in the human genome. We developed Transduction‐Specific Amplification Typing of L1 Active Subfamilies (TS‐ATLAS), which utilizes L1‐transduced genomic sequences, to identify a subset of highly active L1s genome‐wide. TS‐ATLAS enabled the characterization of the putative progenitor of an active disease‐causing L1 lineage, and identified new retrotransposition events within two other "hot" L1 lineages. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>